Ocean Dynamics and Methane Plume Activity in Tatar Strait, Far Eastern Federal District, Russia as Revealed by Seawater Chemistry, Hydroacoustics, and Noble Gas Isotopes - Snyder, Glen Tritch; Yatsuk, Andrey; Takahata, Naoto; Shakirov, Renat; Tomaru, Hitoshi; Tanaka, Kentaro; Obzhirov, Anatoly; Salomatin, Aleksandr; Aoki, Shinsuke; Khazanova, Elena; Maryina, Evgeniya; Sano, Yuji; et al. (Frontiers in Earth Science, 2022)
This investigation presents methane, noble gas isotopes, CTD, and stable isotopic data for water samples collected in Niskin bottles at Tatar Strait during the spring seasons of 2015 and 2019 onboard the Russian R/V Akademik M.A. Lavrentyev. The results are compared to previous research carried out in 1999 in a nearby portion of the Strait and demonstrate that salinity and temperature can change appreciably. The CTD data from 1999 shows warm surface waters underlain by cold subsurface waters. In contrast, the 2015 data show the CTD data that show warm temperatures and high salinity extending down from the surface well into intermediate waters, while the 2019 data show cold surface waters underlain by even colder subsurface waters. CTD data collected above active gas plume sites along Sakhalin Island’s western shore show no substantial difference in temperature or salinity from the non-plume sites, and the methane concentrations at all of the measured sites are significantly above saturation, even in the shallow waters. Hydroacoustic data also suggest the presence of free gas and gas hydrate–coated methane bubbles from the seafloor at least to the base of upper intermediate waters. All of the intermediate and deep Japan Sea Proper waters in Tatar Strait still retain tritiogenic 3He, similar to that observed throughout much of the Japan Sea, indicating limited vertical exchange between these layers and surface waters. An analysis of the δ13C of dissolved inorganic carbon in the seawater shows that positive values are limited to surface waters and that the waters become progressively more depleted in 13C with depth. The results are consistent with research over the past several decades which has shown that ventilation of intermediate and deep Japan Sea Proper water is somewhat limited, while both the temperature and salinity of surface and subsurface water layers within the strait are sensitive to the balance between cold, less saline waters contributed by the Amur River/Primorye Current from the north and warm, saline waters contributed by the Tsushima Current from the south.